Political devolution and employment relations in Great Britain: the case of the Living Wage. Issue 5 (24th August 2020) - Heery, Edmund; Hann, Deborah; Nash, David
Abstract: This article examines the role of the devolved governments of Scotland and Wales in promoting the voluntary Living Wage. It shows that active promotion of the Living Wage standard has emerged in both countries from a broader commitment to an economic policy of 'inclusive growth'. Employment law is not a devolved matter, and the article identifies a broad range of economic incentives and soft forms of regulation that have been used by the devolved governments to promote the Living Wage in the absence of hard power to legislate. Non‐legislative forms of state intervention are often regarded sceptically, but the article shows that the attempts of devolved governments to spread the Living Wage have been impactful, particularly in Scotland.